MicroRNA-210 induces apoptosis in colorectal cancer via induction of reactive oxygen. Issue 1 (December 2016) - Tagscherer, Katrin; Fassl, Anne; Sinkovic, Tabea; Richter, Jutta; Schecher, Sabrina; Macher-Goeppinger, Stephan; Roth, Wilfried
Abstract Background Deregulation of miRNA-210 is a common event in several types of cancer. However, increased expression levels in the cancer tissue have been associated with both poor and good prognosis of patients. Similarly, the function of miR-210 with regard to cell growth and apoptosis is still controversial. Methods Overexpression of miR-210 was performed in HCT116, SW480 and SW707 colorectal cancer (CRC) cell lines. Functional effects of a modulated miR-210 expression were analyzed with regard to proliferation, clonogenicity, cell cycle distribution, reactive oxygen species (ROS) generation, and apoptosis. Furthermore, quantitative real time (RT)-PCR and immunoblot analyses were performed to investigate signaling pathways affected by miR-210. Results We show that in CRC cells miR-210 inhibits clonogenicity and proliferation which was accompanied by an accumulation of cells in the G2/M phase of the cell cycle. Additionally, overexpression of miR-210 results in an increase of ROS generation. Moreover, miR-210 mediated the induction of apoptosis which was associated with an upregulation of pro-apoptotic Bim expression and enhanced processing of Caspase 2. Importantly, inhibition of ROS generation rescued cells from miR-210-induced apoptosis. Conclusions Taken together, miR-210 induces apoptosis in CRC cells via a ROS-dependent mechanism.